A High-Resolution Laser Beam Collimator System with a High-NA lens for a High-Density Ternary Barcode Detection System - Wakaumi, Hiroo (Discoveries in Agriculture and Food Sciences, 2014)
A laser beam collimator system with a high numerical aperture lens and a 1.2 mm aperture masked collimator is proposed to realize a miniature high-resolution ternary barcode detection system in which high-density ternary barcodes can be detected. It was clarified that a 1.2 mm aperture mask combined with a 0.5 NA lens is suitable for maintaining the laser beam width at less than 150 μm over a wide range of more than 4.5 cm. The laser head with this collimator system was applied to a ternary barcode detection system. It was confirmed that the detection system could detect the ternary barcode with a minimum bar width of 0.2 mm over a practical detection range greater than 5 cm (which conventional detection systems could not detect) by optimizing the clamp bias voltage in the clamping circuit to -0.8 V, and the gray bar concentration to 58 %. Barcode detection results also showed that an optimized mask aperture for achieving a maximum detection range for the barcode with a 0.2 mm minimum bar width was 1.2 mm. This collimator system has potential applications in high-speed, high-resolution ternary or binary barcode detection systems.